CONCERT MUSIC VERSUS THE MUSIC OF THE SOUND FILMS - Aaron FAZAKAS (Studia Universitatis Babeş-Bolyai. Musica)
Concert (independent) music, mostly classical, has largely and decisively influenced the emergence and development of cinematography, but, just like all the other independent arts, mostly remodelled to fit the requirements imposed by the sound film, independent music has also undergone major changes which influenced its structure, form and independence, but which became part of a superior synthetic structure from a psychological, artistic and expressive points of view.